INVESTIGATION OF THE OPERATION MODES OF THE BELT-ROPE CONVEYOR ELECTROMECHANICAL SYSTEM WITH VECTOR-CONTROLLED INDUCTION ELECTRIC MOTORS - PECHENIK, Mykolay; BURIAN, Sergey; ZEMLIANUKHINA, Hanna; HODZ, Artem (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Continuous transport systems are the most promising type of movement of loose and artificial materials, have high productivity, technical and economic indicators and are widely used in world practice as main conveyors for the coal and mining industry. A special place in continuous transport is occupied by belt-rope conveyors, which are capable of transporting cargo over a distance of more than 30 km in one stop. As a rule, these main conveyors do not provide for the adjustment of movement parameters, the start is carried out using soft start systems. At the same time, such systems have high requirements for the parameters of dynamic modes of operation, the accuracy of working out the given movement program and the level of energy efficiency.The paper proposes a modern electric drive system using vector-controlled induction electric motors. The structure of the electromechanical system is given. A mathematical model of the electromechanical system was built using known methods. As part of the "MATLAB" Simulink application program package, a model for the investigation of dynamic modes of conveyor operation was obtained. On a specific example, a research of dynamic and static modes of conveyor operation with static load and the speed of movement variations of the traction element was carried out. Studies of the accuracy of working out the given law of motion showed that the maximum dynamic error in terms of speed and current is worked out in a time of up to 0.06 s. The maximum level of its amplitude does not exceed 0.33% of the constant speed of movement, which does not cause oscillatory processes in the conveyor and ensures stable operation of the electromechanical system.Investigation of the electromechanical system energy characteristics was conducted. Losses of active power do not exceed 12.5% of the consumed in the entire range of variation of the static load and speed of the traction element. Recommendations for the use of electromechanical systems with vector-controlled induction electric motors in belt-rope conveyors have been formulated.
Keywords: continuous transportation; vector control; belt-rope conveyor; accuracy of work; power losses